Evolution of face-centered-cubic polycrystalline plastic anisotropy under biaxial loading by crystal plasticity finite element method. Issue 3 (30th September 2019) - Zhao, Dan; Xin, Cun; Jin, Tao; Yan, Xiaopeng; Ma, Shenggguo; Wang, Zhihua
Abstract : Purpose: The purpose of this study to analyze the plastic anisotropy of 6061 aluminum alloy with finite deformation using crystal plasticity finite element method. Design/methodology/approach: A representative volume element (RVE) model was constructed by Voronoi tessellation. In this model, grain shapes, grain orientations and distribution of grains were involved. The mechanical response of the component under composite loading was tested using specify cruciform specimen. Moreover, different stress and strain states in the specific central region were analyzed to reveal the effects of complex loading. Findings: We calculated the influence of misorientation of adjacent grains as well as the evolution of the micro structure's plastic deformation on the macroscopic deformation of the structure. Geometry design for the cruciform specimen helps obtain a homogenous distribution of the stress and strain at the specimen center. In this process, the initial grain orientation is also an important factor, and the larger misorientations between special grains may cause greater stress concentration. Originality/value: The influence of micro-scale factors on macro-scale plastic anisotropy of AA6061 is analyzed using RVE model and cruciform specimen, and they offer a reference for related research.